Effective Utilization of Synthesized FeS2 for Improving Output Performance of Polycrystalline Silicon Solar Cell. (8th October 2022) - Chinnasamy, Moganapriya; Rathanasamy, Rajasekar; Sivaraj, Santhosh; Velu Kaliyannan, Gobinath; Palanisamy, Manivasakan; Pal, Samir Kumar; Uddin, Md. Elias
Abstract : Solar cells are capable of converting light energy into electrical energy and can completely replace the utilization of fossil fuel energy resources. The current research work majorly concentrates on the development and coating of antireflection materials over the front contact of silicon solar cells. Ferrous disulphide was one of the wide band gap semiconductors employed as a catalytic electrode (in DSSCs), counter electrode (in QDSSs), and solar energy harvester. FeS2 was synthesized through the hydrothermal method. The antireflective coating was performed over solar cells through the electrospraying technique. It was found that the antireflective material was distributed evenly over the coating substrate at 2 ml/h for 30 (F1), 60 (F2), 90 (F3), and 120 (F4) min. The coated solar cells were examined under neodymium light illumination mimicking sunlight. The effect of electrosprayed FeS2 films adhered over the front contact of solar cells was evaluated using various characterization techniques. The maximum efficiency attained by coated solar cells under indirect light was 19.6%. With the aid of electrospraying, hydrothermally synthesized FeS2 assists incoming photons with energy greater than the bandgap of a procured Si solar cell to take part in the photogeneration process. The maximum Isc and Voc of 38.08 mA/cm 2 and 0.655 V were achieved for the F3 solar cell under neodymium irradiation.